A CO2 adsorption dominated carbon defect-based electrocatalyst for efficient carbon dioxide reduction. Issue 3 (23rd December 2019) - Wu, Qilong; Gao, Jin; Feng, Jianrui; Liu, Qian; Zhou, Yunjie; Zhang, Shengbo; Nie, Manxiu; Liu, Yang; Zhao, Jiongpeng; Liu, Fuchen; Zhong, Jun; Kang, Zhenhui
Abstract : A defect-derived metal-free electrocatalyst with appropriate CO2 adsorption for efficient carbon dioxide reduction. Abstract : Controlling interface gas adsorption properties of carbon materials is a prerequisite for exploiting efficient metal-free electrocatalysts but it is usually ignored. Herein, we fabricate a hierarchical porous carbon electrocatalyst with defect (DHPC) by carbon thermal reaction, which shows good CO2 RR selectivity and stability. The experimental results indicated that the carbon defect might be the active center for efficient CO2 RR performance because it can serve as a Lewis base center and provide an appropriate CO2 -chemisorption energy. Moreover, X-ray absorption spectroscopy (XAS) results demonstrated that the carbon defect can induce a reversible carbon–carbon interface with CO2 gas molecule, which would be further strengthened under an applied bias. Besides, the 13 CO2 isotope labelling experiment and density functional theory calculations further confirmed that the high CO2 RR performance of DHPC comes from its intrinsic defect sites. This study not only provides a new avenue and concept to design CO2 RR electrocatalysts but also, to some extent, indicates a possible catalytic mechanism for carbon defect-based electrocatalysts.